Research Unit of Physics, Chemistry and Biology of Atmospheric Composition and Climate Change: overview of recent results - Kulmala, M.; Hari, P.; Laaksonen, A.; Vesala, T.; Viisanen, Y. (Boreal Environment Research Publishing Board, 2024)
In this paper we present research methods and recent results obtained within activities of the Research Unit of Physics Chemistry and Biology of Atmospheric Composition and Climate Change, which is one of the centres of excellence of the Academy of Finland. The centre forms an integrated attempt to understand various, but interlinked, biosphere–atmosphere interactions applying inter- and multidisciplinary approaches in a coherent manner. The main disciplines used cover aerosol and environmental physics, atmospheric chemistry and physics, micrometeorology, forest ecology and ecophysiology. The main objective of the centre is to study the importance of aerosol particles on climate change. Our scientific approach that starts from basic nucleation theories, is followed by detailed aerosol dynamic/atmospheric chemistry models and well-defined laboratory experiments, and ends with wide continuous field measurements in our research stations and 3D modelling. During the last years the joint efforts within our centre of excellence and the Nordic centres of excellence BACCI (devoted to atmospheric physics and chemistry) and NECC (devoted to carbon balance of northern ecosystems) have increased strongly. A thorough understanding of physical, meteorological, chemical and ecophysiological processes obtained by individual research groups lays the foundation of a unique possibility to study biosphere–aerosol–cloud–climate interactions, or the interplay between carbon exchange, BVOC emissions and formation of new aerosol particles. The necessary requirement is jointly working, real inter-, multi- and cross disciplinary teams. The core of activities is in continuous measurements and database of atmospheric and ecological mass fluxes and aerosol precursors and CO2-aerosol-trace gas interactions in SMEAR field stations. These are supported by models of particle thermodynamics, transport and dynamics, atmospheric chemistry, boundary layer meteorology and forest growth.